Patterns of genetic differentiation imply distinct phylogeographic history of the mosquito species Anopheles messeae and Anopheles daciae in Eurasia - Brusentsov, Ilya; Gordeev, Mikhail I.; Yurchenko, Andrey A.; Karagodin, Dimitriy A.; Moskaev, Anton V.; Hodge, James M.; Burlak, Vladimir A.; Artemov, Gleb N.; Sibataev, Anuarbek K.; Becker, Norbert; Sharakhov, Igor V.; Baricheva, Elina M.; et al. (Molecular ecology, 2023)
Detailed knowledge of phylogeography is important for control of mosquito species involved in the transmission of human infectious diseases. Anopheles messeae is a geographically widespread and genetically diverse dominant vector of malaria in Eurasia. A closely related species, An. daciae, was originally distinguished from An. messeae based on five nucleotide substitutions in its ribosomal DNA (rDNA). However, the patterns of phylogeographic history of these species in Eurasia remain poorly understood. Here, using internal transcribed spacer 2 (ITS2) of rDNA and karyotyping for the species identification we determined the composition of five Anopheles species in 28 locations in Eurasia. Based on the frequencies of 11 polymorphic chromosomal inversions used as genetic markers, a large-scale population genetics analysis was performed of 1932 mosquitoes identified as An. messeae, An. daciae and their hybrids. The largest genetic differences between the species were detected in the X sex chromosome suggesting a potential involvement of this chromosome in speciation. The frequencies of autosomal inversions in the same locations differed by 13%-45% between the species demonstrating a restricted gene flow between the species. Overall, An. messeae was identified as a diverse species with a more complex population structure than An. daciae. The clinal gradients in frequencies of chromosomal inversions were determined in both species implicating their possible involvement in climate adaptations. The frequencies of hybrids were low similar to 1% in northern Europe but high up to 50% in south-eastern populations. Thus, our study revealed critical differences in patterns of phylogeographic history between An. messeae and An. daciae in Eurasia. This knowledge will help to predict the potential of the malaria transmission in the northern territories of the continent.
Zuerst veröffentlicht: 13. September 2023
Gesehen am 13.11.2023